Inheritance and wealth tax aspects of emigration and immigration of individuals : proceedings of a seminar held in Oslo, Norway, in 2002 during the 56th Congress of the International Fiscal Association /: proceedings of a seminar held in Oslo, Norway, in 2002 during the 56th Congress of the International Fiscal Association. (2016) - Unknown
No abstract available